Effect of different doses of saponins and salinity on giant tiger prawn Penaeus monodon and Nile tilapia Oreochromis niloticus. Issue 1 (May 2021) - Yasir, I; Tresnati, J; Aprianto, R; Yanti, A; Bestari, A D; Tuwo, A
Abstract: The Nile Tilapia Oreochromis niloticus is considering as a pest in shrimp farming ponds, as it is a shrimp competitor and predator of benthic organisms. This study aims to determine the effective and efficient saponins doses to eradicate tilapia without causing shrimp mortality. The study used two different saponins doses (200 kg/ha and 100 kg/ha) with seven different levels of salinity (5, 10, 15, 20, 25, 30, 35 ppt). The saponins doses used in this study had no effect on shrimp mortality, but had a significant effect on mortality of nile tilapia. The mortality of nile tilapia was 100% for all treatments. The death time of nile tilapia decreased significantly with increasing salinity. Longest nile tilapia death time was found at 10 ppt water salinity; this salinity is close to that of body fluids (14 ppt). The greater the difference between the ion content of body fluids and water ions in the test media, the faster the time of death. The effects of bleeding on the operculum, pectoral and caudal fins are more severe at high salinity. It is advisable not to increase the saponins doses, use the same saponins doses at any salinity, because predatory and competitive fish will die at any salinity.